2021
DOI: 10.1016/j.clnesp.2020.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of probiotic and alpha-lipoic acid supplements, separately or in combination on the anthropometric indicators and maintenance of weight in overweight individuals

Abstract: Background & aims: Weight loss after proper diet is one of the main topics in nutrition. This study was designed to evaluate the effects of probiotic and alpha-Lipoic acid (ALA) supplements on the anthropometric indicators and maintenance of weight in overweight individuals. Methods: This study consisted of two phases of weight loss (8 weeks) and weight maintenance (16 weeks). Eighty-eight overweight participants were randomly divided into 4 groups in phase 1: isocaloric diet with probiotic (500 mg), an isocal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The general characteristics of the included studies are outlined in Table S4. Trials were published between 1996 and 2023, and were carried out in Asia, 12,27–31,77–81,84–229 Europe, 230–262 America,…”
Section: Resultsmentioning
confidence: 99%
“…The general characteristics of the included studies are outlined in Table S4. Trials were published between 1996 and 2023, and were carried out in Asia, 12,27–31,77–81,84–229 Europe, 230–262 America,…”
Section: Resultsmentioning
confidence: 99%
“…Eligible trials were published between 1997 and 2021. The studies were performed in Iran ( 28 , 31 , 40 , 42 ), United States ( 41 , 45 , 47 ), Mexico ( 17 ), Italy ( 43 ), Korea ( 44 ), and Germany ( 46 ). The intervention duration of selected RCTs ranged from 8 to 48 weeks, with a sample size ranging from 12 to 155 participants.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical trials with α-lipoic acid treatment have shown a statistically significant short-term reductions in weight, BMI, body fat, and waist circumference, compared to placebo [ 218 , 219 , 220 , 221 ]. Table 11 shows the clinical effects of α-lipoic acid on obesity and related comorbidities, according to clinical trials and systematic reviews with meta-analyses of clinical trials found in the scientific literature.…”
Section: Molecules With Demonstrated Clinical Efficacy In the Prevent...mentioning
confidence: 99%